Prenatal case report of Barth syndrome caused by novel TAFAZZIN mutation: Clinical characteristics of fetal dilated cardiomyopathy with ascites - Zhao, Xuliang; Li, Xu; Sun, Weiwei; Jia, Jian-an; Yu, Min; Tian, Ruixia (Frontiers in Pediatrics, 2022)
Barth syndrome (BTHS) is a rare X-linked recessive genetic disease, which appears in infancy with myocardial and skeletal muscle diseases, neutropenia, growth retardation, and other clinical features. TAFAZZIN is the pathogenic gene of BTHS, which encodes the tafazzin protein of the inner membrane of the mitochondria, a phosphatidyltransferase involved in cardiolipin remodeling and functional maturation. At present, BTHS has been widely reported, but prenatal cases are rare. We report a 24+4-week fetus with clinical manifestations including left ventricular insufficiency and ascites. After induced labor, whole exome sequencing detection of fetal skin tissue showed that TAFAZZIN had the mutation c.311A>C/p.His104Pro and that his mother was the carrier. This His104Pro mutation has hitherto not been reported, and it is rated as likely to be pathogenic according to the American College of Medical Genetics and Genetics guidelines. Molecular dynamics and protein expression experiments on the His104Pro mutation showed that the stability of the local protein structure and protein expression were reduced. In conclusion, the case presented in this study enriches our knowledge of the TAFAZZIN mutation spectrum and suggests that His104Pro may lead to cardiac structural abnormalities in the early embryo. The possibility of BTHS should be considered when an abnormal cardiac structure or ascites appear in a prenatal ultrasound.